PERAN KEPEMIMPINAN DALAM MENEGAKKAN DISIPLIN KERJA APARAT DESA (Studi Kasus di Desa Tewah Pupuh Kecamatan Benua Lima) Kabupaten Barito Timur (p3m.stiatabalong.ac.id, 2022)
The role of leadership in the village government in carrying out its duties and obligations is assisted by village officials to run the wheels of the village government. Government Regulation Number 6 of 2014 concerning Villages, which contains